Direct Cash Assistance from Village Funds (BLT-DD) in Watulaney Village, Lembean Timur District - Limpele, James; Kairupan, Sisca Beatrix; Sendouw, Recky H E (International Journal of Information Technology and Education, 2025)
This study aims to analyze the implementation of the Direct Cash Assistance Program from Village Funds (BLT-DD) in Watulaney Village, Lembean Timur District, with a specific focus on the factors influencing the program’s effectiveness. Using a qualitative approach and the policy implementation theory by Van Meter and Van Horn (1975), the study evaluates six key variables: policy standards and objectives, resources, inter-organizational communication, characteristics of the implementing agency, implementers’ attitudes, and the social, economic, and political conditions. The findings indicate that the implementation of BLT-DD in Watulaney Village faces several challenges, including mistargeted beneficiaries, delays in fund disbursement, and limitations in human resources and technological infrastructure. Although supported by regulations such as the Ministry of Villages Regulation No. 6 of 2020 and No. 13 of 2023, the program still encounters difficulties in data collection, verification, and coordination among stakeholders. On the other hand, community participation and transparency in village meetings are identified as significant supporting factors. This study recommends improving the accuracy of recipient data, strengthening the capacity of village officials through training, and optimizing the use of digital technology for data management and reporting. Hence, the BLT-DD program is expected to become more effective in achieving its goals of poverty alleviation and enhancing the welfare of the residents of Watulaney Village.